JURISDICTIONAL DECISIONS AND CONSEQUENCES OF THEIR ADOPTION BEST PRACTICES AND CASE ANALYSES (TSUL LEGAL REPORT, 2026)
There are a broad variety of views, both in theory and case law, on the grounds for determination of the power of arbitrators to resolve disputes under their private power. For instance, while some scholars assume that authority is derived from the arbitral treaty as an item of approval necessary for the аrbitrаtiоn process, others assume that authority exists irrespective of any type of arrangement as an intrinsic force of the arbitral tribunal. In addition, a great number of writers apply the legislation of any state in which the аrbitrаtiоn arrangement is required to be applied to the definition of authority in the regulation of the arbitral seat. On the contrary, some scholars argue that the authority of arbitrators to exercise their private power should be separated from usual norms, rendering it impossible to rely on clauses of domestic law. Although these various foundations appear to be mutually exclusive at first glance, some writers nonetheless define them.